Technology Acceptance Model and Theory of Planed Behavior: Mapping Literature Review - Banjarnahor, Astri Rumondang (Manunggal Halim Jaya, 2021)
TAM (Technology Acceptance Model) is a technology application model that adopts the Theory of Reasoned Action (TRA) from Fishbein and Ajzen (1975) which is used to see the level of use of respondents in receiving information technology (Kaffashan Kakhki et al., 2020). This TRA is composed of the basic assumption that every human being behaves consciously in self-control and considers the use of available information for use in his life. Ajzen and Fishbein (1975) state that two determining factors can influence a person's intention in doing a certain act, the first is related toattitude towards behavior) and the next influence is social influence, namely subjective norms (subjective norms). This study uses a bibliometric literature review approach with a sample mapping literature of 17 articles regarding planned behavior theory approaches reference articles from 2020 - 2021 under Scopus indexed journal. Our proposition state result the correlation Theory of planned behavior theory and TAM in the aspect of the field of management (e.g., marketing, Technology, E-Commerce) make a positive contribution as a grounded theory to explain the variable antecedent and also its correlation to other theories.